Knowing And Unknowing: Pathways To Peaceful Living In Personal And Social Contexts - Thakur , Radheshyam (GS WOW: Wisdom of Worthy Research Journal, 2025)
The interplay between “knowing” and “unknowing” plays a crucial role in fostering peaceful living at both personal and social levels. This article explores how balancing knowledge and acceptance of uncertainty contributes to personal growth, social harmony, and conflict resolution. Drawing on epistemology, psychology, and conflict studies, the article synthesizes relevant theories—including Keats’s concept of negative capability and Mezirow’s transformative learning theory —alongside personal reflections and practical examples. The findings suggest that knowledge offers stability, direction, and empowerment, while unknowing fosters flexibility, adaptability, and humility. Together, they enhance intercultural understanding, reduce prejudice, and promote emotional resilience. Embracing both certainty and uncertainty cultivates empathy, openness, and adaptability. Integrating knowing with unknowing enables individuals to navigate life’s complexities more peacefully, supporting both personal and collective growth. The article recommends further research on applying this dual awareness in education, conflict resolution, and community development.